Comprehensive analysis of charge carriers dynamics through the honeycomb structure of graphite thin films and polymer graphite with applications in cold field emission and scanning tunneling microscopy - Allaham, Mohammad Mahmoud Mohammad; Daradkeh, Samer Issa Abdel Razzaq; Al-Braikat, Hatem; Dallaev, Rashid; Burda, Daniel; Košelová, Zuzana; Al-Akhras, M-Ali; Jaber, Ahmad; Mousa, Marwan; Sobola, Dinara; Kolařík, Vladimír; Knápek, Alexandr (ELSEVIER, 2024)
Polymer graphite electron sources have performed satisfactorily as field emission emitters and scanning tunneling microscopy probes in the past few years. However, the emission process was characterized by limited total emission currents. This paper introduces the elemental, vibrational, electronic structure, and optical analysis of polymer graphite and glass-graphite composite field emission cathodes to study these limitations. Moreover, the field emission characteristics are studied including the changes in the potential energy barrier of the used materials and structures. Among the studied structures, the cathodes prepared from graphite thin films deposited on a micropointed glass substrate (film-GMF) showed superior performance as random field emission arrays. This includes obtaining much higher emission current values 20 times) and lower threshold voltages 1/2) compared to the results obtained from polymer graphite samples. The enhancement factor in such emitters is believed to be the three-dimensional honeycomb structure of graphite. Moreover, the study includes applying graphite coatings to tungsten nano-field emission cathodes and scanning tunneling microscopy probes, which improves the performance of such cathodes/probes in both microscopic techniques.

Polymer graphite electron sources have performed satisfactorily as field emission emitters and scanning tunneling microscopy probes in the past few years. However, the emission process was characterized by limited total emission currents. This paper introduces the elemental, vibrational, electronic structure, and optical analysis of polymer graphite and glass-graphite composite field emission cathodes to study these limitations. Moreover, the field emission characteristics are studied including the changes in the potential energy barrier of the used materials and structures. Among the studied structures, the cathodes prepared from graphite thin films deposited on a micropointed glass substrate (film-GMF) showed superior performance as random field emission arrays. This includes obtaining much higher emission current values 20 times) and lower threshold voltages 1/2) compared to the results obtained from polymer graphite samples. The enhancement factor in such emitters is believed to be the three-dimensional honeycomb structure of graphite. Moreover, the study includes applying graphite coatings to tungsten nano-field emission cathodes and scanning tunneling microscopy probes, which improves the performance of such cathodes/probes in both microscopic techniques.
Comprehensive analysis of charge carriers dynamics through the honeycomb structure of graphite thin films and polymer graphite with applications in cold field emission and scanning tunneling microscopy
Keywords: Cold field emission; Glass-graphite interface; Graphite microflakes; LiteScope; Polymer graphite; Cold field emission; Glass-graphite interface; Graphite microflakes; LiteScope; Polymer graphite